The shape of Christian priesthood today. Issue 5 (September 2022) - Platten, Stephen
Periodically, the concept of an ordained ministry has been criticized and even dismissed. A generation ago this was addressed in the work of Alec Graham and Michael Ramsey, who argued for a clear model of the distinctiveness but integral nature of lay and ordained ministry. Similar questions have been raised recently. On both occasions a sacramental model has been proposed. This has been expounded from a number of different theological directions. Sacramentality lies at the heart of an intellectually and spiritually underpinned pattern both of the Church and of Christian ministry.